(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the biosafety management practices and laboratory biosafety practices of staff at the Can Tho Blood Transfusion Hematology Hospital in 2024. Subjects and Methods: A cross-sectional descriptive study was conducted involving all laboratory staff and relevant records related to biosafety management. Results: A survey conducted in four laboratories with 70 staff members revealed several limitations in biosafety management at the hospital. Although the biosafety management system is relatively comprehensive, only three out of four laboratories have designated personnel responsible for biosafety. In terms of infrastructure, only two out of three laboratories fully meet the required standards. Most staff members demonstrate a correct understanding of biosafety regulations and adhere well to personal protective equipment usage; however, proper technical practices in biosafety cabinets are limited, particularly regarding disinfection procedures and cabinet operation protocols. Conclusion: It is essential to enhance training, supervision, and updating of biosafety regulations, as well as standardize processes and conduct regular